UI/UX Design for New Student Admission Queue System Using the Design Thinking Method - Antonius Antonius; Genrawan Hoendarto; Tony Darmanto; Sandi Tendean (Information Technology and Science (ITScience), 2026)
The new student admission process (PMB) often faces queue management issues, as prospective students must wait in line to submit documents, verify data, and consult staff. This study designed a user interface (UI) for a PMB queueing system at Universitas Widya Dharma Pontianak (UWDP) using the Design Thinking approach. The UI was created with Figma as an interactive prototype and later developed into a web-based application. Design Thinking consists of five stages: empathize, define, ideate, prototype, and test to ensure the solution meets user needs. During empathize, interviews and observations were conducted with students and the PMB committee to identify queue-related problems. The findings were turned into user personas and problem statements in the define stage. Next, the ideate stage produced prioritized solution ideas, followed by a user interface prototype in Figma. The resulting prototype visualizes the queueing process from registration to student call-outs, featuring remote queue number retrieval, and the real-time queue display. The prototype was tested using the System Usability Scale (SUS) questionnaire with 30 prospective students. The average SUS score was 78.5, classified as